Test-retest reliability of ski-specific aerobic, sprint, and neuromuscular performance tests in highly trained cross-country skiers - Bucher, E.; Millet, G. P.; Wehrlin, J. P.; Steiner, T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Purpose Laboratory tests are commonly performed by cross-country (XC) skiers due to the challenges of obtaining reliable performance indicators on snow. However, only a few studies have reported reliability data for ski-specific test protocols. Therefore, this study examined the test-retest reliability of ski-specific aerobic, sprint, and neuromuscular performance tests.